Modification of the Adjustment Disorder New Module20 (ADNM‐20) for Use in Military Environments (ADNM‐20‐MIL): A Delphi and Pilot Study - Jouhayna Bajjani‐Gebara; Dawnkimberly Hopkins; Joan Wasserman; Ryan Landoll; Margaux Keller (International Journal of Methods in Psychiatric Research)
ABSTRACT Objectives Despite its high prevalence and strong linkages with dangerous health outcomes, research on Adjustment Disorder (AjD) is hindered by lack of diagnostic clarity. AjD is categorized as a stress‐related disorder, highlighting the important role of the stressor(s) on AjD symptom onset and severity. The military community shows increased risk for AjD, and existing tools do not capture the stressors most relevant and appropriate to this unique community. A diagnostic assessment tool developed specifically for this specialized population may provide critical capability to clinical assessment. Methods A Delphi method was used to create a military‐specific version of the standard assessment for Adjustment Disorders (ADNM‐20), named ADNM‐20‐MIL. This tool was pilot‐tested in a sample of U.S. Active Duty Service Members (ADSMs) with AjD diagnoses. Results Throughout the Delphi process, military‐specific stressors were identified and integrated into the ADNM‐20‐MIL, then refined and validated, ensuring their applicability and relevance to the military context. Conclusions The ADNM‐20‐MIL will enable timely diagnosis and targeted treatment for AjD, which remains a highly prevalent and destabilizing diagnosis in ADSMs.